Rare earth element enrichment in Palaeoproterozoic Fengzhen carbonatite from the North China block. Issue 15 (17th November 2016) - Feng, Meng; Xu, Cheng; Kynicky, Jindrich; Zeng, Liang; Song, Wenlei
ABSTRACT: Carbonatites are characterized by the highest concentration of rare earth elements (REEs) of any igneous rock and are therefore good targets for REE exploration. Supergene, hydrothermal, and magmatic REE deposits associated with carbonatites have been widely studied. REE enrichment related to fluorapatite metasomatism in Fengzhen carbonatites in the North China block is reported in this study. REE minerals (monazite, britholite, and Ca-REE-fluorocarbonates) associated with barite and quartz formed as inclusions within the fluorapatite and externally on its surface. Monazite, allanite, barite, and quartz occur as rim grains on the edges of the fluorapatite. Zoned fluorapatite was observed and showed varying chemical composition. Based on back-scattered electron imaging, the dark domains with mineral inclusions contain lower Si (0.3–0.6 wt.% SiO2 ) and light REE (LREE) [0.36–1.54 wt.% (Y+LREE)2 O3 ] contents than inclusion-poor areas [0.7–1 wt.% SiO2 ; 2.16–4.51 wt.% (Y + LREE)2 O3 ]. This indicates a dissolution–re-precipitation texture. Different types of monazites were distinguished by their chemical compositions. Monazite inclusions have lower La2 O3 contents ( 13 wt.%) and La/Ndcn ( 3) ratios than those (18–26 wt.% and 10–14 for La2 O3 and La/Ndcn, respectively) growing externally on the fluorapatite. REE enrichment in the metasomatic fluorapatites is related to different stages of carbonatitic liquids. The early carbonatite-exsolved fluids metasomatized the fluorapatites to form REE mineral inclusions. The late carbonatitic fluids from carbonatite magmas that underwent strong fractional crystallization were enriched in REEs, Al, and Fe and metasomatized the fluorapatites to produce allanite and monazite rim grains.